THE EFFECT OF THE FABLE COTTAGE CHANNEL OF YOUTUBE TOWARDS STUDENTS’ SPEAKING SKILLS - Taufik Suadiyatno; Anggito Abimayu (JOETAL: Journal of Education, Teaching and Learning, 2024)
Students face significant barriers to effective self-expression, including speaking apprehension, diminished motivation, and confidence deficits. Traditional teaching methods, such as the Silent Way, exacerbate these issues. To overcome these challenges, educators must adopt innovative instructional strategies that foster active learning, promote speaking skills, and encourage student engagement. The Fable Cottage channel transforms language learning into an immersive experience, leveraging storytelling to enhance linguistic proficiency. Departing from traditional textbook-based instruction, this approach fosters vocabulary expansion, cultural awareness, creativity, critical thinking and effective communication skills through collaborative project-based learning. The aim of this study was to determine whether the Fable Cottage YouTube channel has an effect on students' speaking skills. This study was a quantitative method using a pre-experimental design. The sample of this study consisted of 36 students. Based on the data analysis the results indicated a positive effect on the English-speaking skills of students who were taught using the Fable Cottage YouTube channel, compared to those who experienced traditional teaching methods. Students reported that the YouTube videos helped them infer the meaning of unfamiliar words and improved their speaking skills. The implementation of The Fable Cottage Channel YouTube videos yielded significant enhancements in students' speaking skills. The researchers recommended that language teachers integrate the Fable Cottage YouTube channel when teaching speaking.